PKM Empowering Millennial Generation as Corpse Bathing Attendants Among Mosque Youth in Makassar: Pengabdian Masyarakat - Muhammadong; Nurhilaliyah; Khaerunnisa; Sitti Muthmainnah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Death is an undeniable axiom, as it is a divine decree and an absolute right under God's authority. In Islamic teachings, human rights must be fulfilled not only during life but also at the time of death. The involvement of millennial youth as funeral bathing attendants represents a progressive step that should be appreciated, as it reflects their commitment to fulfilling religious duties and meeting community needs. Mosque youth serve as a pillar of the millennial generation who can ease societal burdens through their innovative work and creativity. This community service program (PKM) aims to empower the millennial generation in carrying out religious obligations, as their potential is more energetic and capable of fulfilling fardhu kifayah responsibilities. The methods used include discussion sessions to provide input and knowledge about the Islamic ritual of bathing the deceased. Practical sessions are intended to teach the proper procedures so that they can be easily implemented within the community. A question-and-answer method helps ensure that the participants fully understand the material presented. Demonstrations are used to convey tips and techniques in a clearer and more accessible way. Lastly, evaluation methods are employed to measure the participants’ understanding and competence regarding the material delivered.